1988
DOI: 10.1128/aac.32.5.782
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions of ciprofloxacin and extended-spectrum beta-lactams or aminoglycosides against multiply drug-resistant Pseudomonas maltophilia

Abstract: The susceptibility of 28 clinical isolates of Pseudomonas maltophilia to 16 antimicrobial agents was determined in vitro by a standard agar dilution method with inoculum sizes of 104 and 106 CFU. All isolates exhibited multiple drug resistance. Nine isolates were selected for studies of combinations of ciprofloxacin with seven antipseudomonal ,-lactams and three aminoglycosides by a checkerboard agar dilution technique. Synergistic or additive combinations of ciprofloxacin in clinically achievable concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Chow et al (8) previously investigated synergy between ciprofloxacin and various ␀-lactams against S. maltophilia by the checkerboard method. Although they found that synergy occurred most frequently between ciprofloxacin and ceftazidime, synergy or additivity was demonstrated for only 33% of their strains at clinically achievable levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chow et al (8) previously investigated synergy between ciprofloxacin and various ␀-lactams against S. maltophilia by the checkerboard method. Although they found that synergy occurred most frequently between ciprofloxacin and ceftazidime, synergy or additivity was demonstrated for only 33% of their strains at clinically achievable levels.…”
Section: Discussionmentioning
confidence: 99%
“…Of commonly used antimicrobial agents, only trimethoprim-sulfamethoxazole has been found to be consistently active in vitro against this organism (10,17). Available quinolones such as ciprofloxacin and ofloxacin are marginally active, with MICs for susceptible isolates clustering around the breakpoint (1,4,9,(12)(13)(14). Clinafloxacin (CI-960, PD 127391) and PD 131628 (the active component of the prodrug CI-990) are two new fluoroquinolones with improved activity against gram-positive cocci, gramnegative nonfermenters, and anaerobes (5,6,8,9,12,16).…”
mentioning
confidence: 99%
“…Its natural resistance restricts the choice of antibiotics for use in the treatment of infected patients (1,2,11,16), and quinolones have been considered as a possible option for therapy (17). The agar diffusion method has revealed a particular phenotype of quinolone susceptibility for this species (12).…”
mentioning
confidence: 99%